Similar and specific immunotropic effects of sulfate-chloride sodium-magnesium mineral waters "Myroslava" and "Khrystyna" of Truskavets’ spa in healthy female rats - Badiuk, Nataliya; Popovych, Dariya; Hrytsak, Myroslava; Ruzhylo, Sofiya; Zakalyak, Nataliya; Kovalchuk, Galyna; Mel’nyk, Oksana; Zukow, Xawery (Journal of Education, Health and Sport, 2021)
Background. Earlier in an experiment on rats, we showed that newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa has a significant modulating effect on the parameters of metabolism and the autonomic nervous and endocrine systems. In this study, conducted in line with the concepts of neuroendocrine-immune complex and functional-metabolic continuum, data on the immunomodulatory effects of these waters on the same rats. Materials and Methods. Experiment was performed on 50 healthy female Wistar rats 230-290 g divided into 4 groups. Animals of the first group remained intact, using tap water from drinking ad libitum. Rats of the second (control) group for 6 days administered a single tap water through the tube at a dose of 1,5 mL/100 g of body mass. The rats of the main groups received the water "Myroslava" and "Khrystyna". The object of the study were the immune parameters of the thymus, spleen and blood. Results. The method of discriminant analysis revealed 12 parameters, according to which the animals loaded with mineral waters differed significantly from both control and intact animals. Classification accuracy is 86%. However, the difference between the immunotropic effects of mineral waters of different mineralization concerns only 9 parameters. Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa have both similar and specific immunomodulating effects on healthy old female rats with weekly use. This provides a basis for preclinical studies.